MR Angiography Follow-Up 5 Years after Coiling: Frequency of New Aneurysms and Enlargement of Untreated Aneurysms - Sprengers, M.E. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: Patients with intracranial aneurysms are at risk for future development of new aneurysms and growth of additional untreated aneurysms. Because in previous long-term studies duration of follow-up varied widely, the time interval after which screening could be effective remains largely unknown. The purpose of this study was to assess the incidence of de novo aneurysm formation and the growth of additional untreated aneurysms in patients with coiled aneurysms followed up with MR angiography (MRA) after a fixed period of 5 years. MATERIALS AND METHODS: In 65 patients with coiled intracranial aneurysms, high-resolution 3T MRA was performed 5.1 ± 0.2 years after coiling. MRA follow-up imaging was compared with MRA or CT angiography at the time of coiling. Additional aneurysms detected at MRA follow-up were classified as unchanged, grown, de novo, or incomparable with previous imaging. RESULTS: In 13 of 65 patients (20%), 24 additional aneurysms were found. Four aneurysms were incomparable with previous imaging and 2 of these were clipped. Of the remaining 20 additional aneurysms, 1 was de novo, 1 had grown slightly, and 18 were unchanged. The incidence of de novo aneurysm formation after 5 years was 1.54% (95% confidence interval, 0.01–9.0%). For additional aneurysms known at the time of initial coiling and for the 1 de novo aneurysm, no treatment was indicated. CONCLUSIONS: MRA screening 5 years after coiling for detection of de novo aneurysms and growth of additional untreated aneurysms has a low yield in terms of finding aneurysms that need to be treated.